ИСКУССТВЕННЫЙ ИНТЕЛЛЕКТ В СОВРЕМЕННОЙ МЕДИЦИНЕ: ВОЗМОЖНОСТИ, РИСКИ И ПЕРСПЕКТИВЫ РАЗВИТИЯ (Uzbekistan Open Conference, 2026)
This article examines the current state and prospects of implementing artificial intelligence (AI) technologies into the healthcare system. The main directions of applying machine learning and neural network algorithms in clinical medicine are analyzed, including radiation diagnostics, predictive analytics, drug development, and treatment personalization. Special attention is paid to problems related to digitalization, in particular, the protection of personal data, ethical dilemmas, the "black box" problem in decision-making algorithms, and legal liability.